A multilevel approach to explain child mortality and undernutrition in South Asia and Sub-Saharan Africa - Kenneth Harttgen; Mark Misselhorn (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
While undernutrition among children is very pervasive both in Sub- Saharan Africa and South Asia, child mortality is rather low in South Asia. In contrast to that Sub-Saharan African countries su er by far the worst from high rates of child mortality. This di erent pattern of child mortality and undernutrition in both regions is well known, but approaches using aggregated macro data have not been able to explain it appropriately. In this paper we analyze the determinants of child mortality as well as child undernutrition based on DHS data sets for a sample of ve developing countries in South Asia and Sub-Saharan Africa. We investigate the e ects of individual, household and cluster socioeconomic characteristics using a multilevel model approach and examine their respective in uences on both phenomena. We nd that the determinants of child mortality and undernutrition di er signi cantly from each other. Access to health infrastructure is more important for child mortality, whereas the individual characteristics like wealth and educational and nutritional characteristics of mothers play a larger role for anthropometric shortfalls. Although very similar patterns in the determinants of each phenomenon are discernable between countries, there are large di erences in the magnitude of the coe cients. Besides regressions using a combined data set of all six countries show, that there are still signi cant di erences between the two regions although taking account of a large set of covariates.
Keywords: C40; I12; I31; I32; O57; 330; Armut; Entwicklungsländer; Kindersterblichkeit; Unterernährung; Südasien; Afrika südlich der Sahara